Merging decision support and expert system technologies : an evolutionary analysis and proposals for an architectural framework - Smith, Gideon Daniel (Accounting and Accountability in Africa, 2024)
The fact that competence in decision-making differentiates the effective manager from the ineffective manager <Harrison.1981: l>J makes decision-making one of management's printiple concerns <Uliana.1986:1). The implication of this for DSS research is that means have to be sought that could contribute towards raising the quality of managerial decision-making. The objective of this research is therefore. f1·rstly. to establish whether traditional DSS is adequately equipped to adapt to changing user needs. Secondly, alternative theoretical foundations of Expert System <ES> enhanced DSS are examined.